The Effects of Service-Learning Participation on Pre-Internship Educators’ Teachers’ Sense of Efficacy - Stewart, Trae; Allen, Kay W.; Bai, Haiyan (Alberta Journal of Educational Research, 2011)
This study aimed to determine if pre-internship teacher education students’ participation in service-learning activities in K-12 classrooms would significantly affect their teachers’ sense of efficacy (TSE). A secondary focus sought to determine if one type of service-learning activity (e.g., whole-class instruction) would affect teacher efficacy more than another (e.g., small-group tutoring). Findings revealed that pre-internship service-learners in both types of service-learning activities increased significantly in their TSE. However, neither type of service-learning activity was superior to the other as measured by the minimally accepted .05 level. The discussion focuses on factors shared between the two service-learning designs that might mediate a positive mastery experience. L’objectif de cette étude était de déterminer si la participation par des étudiants en pédagogie à des activités de bénévolat dans des classes de la maternelle à la 12e année augmenterait de façon significative leur sentiment d’être efficaces comme enseignants. Un deuxième objectif consistait à déterminer si un type d’activité de bénévolat (par ex. l’enseignement à toute la classe) affecterait l’efficacité d’un enseignant plus qu’une autre (par ex. le tutorat à de petits groupes). Les résultats indiquent que les deux types d’activité ont accru de façon significative le sentiment d’efficacité comme enseignants chez les étudiants bénévoles. Toutefois, les paramètres selon le seuil minimal de 0,05 ont révélé qu’aucune activité n’était supérieure à l’autre. La discussion porte sur des facteurs communs aux deux activités de bénévolat et qui pourraient entrainer une expérience d’apprentissage fructueuse.